Peran Supervisi Akademik Dalam Meningkatkan Kompetensi Pedadogik Dan Kinerja Guru Di SMA Negeri 1 Parakansalak Kabupaten Sukabumi - Siti Nuraeni Mitra; Siti Qomariyah; Irma Hermawati; Tintin Handiyati; Cucu Saadah Nursaidah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The quality of learning at SMAN 1 Parakansalak shows a less effective condition, indicated by the low ability of teachers to plan, implement, evaluate, assess learning and follow up on assessment results. The aim of this research is to determine the role of academic supervision in improving pedagogical competence and teacher performance at SMA Negeri 1 Parakansalak Sukabumi Regency. This research uses a descriptive qualitative method with a case study approach, data collection is carried out through observation, interviews and documentation. The results of this research show that the role of academic supervision partially has a positive and significant influence on increasing pedagogical competence and teacher performance at SMAN 1 Parakansalak, Sukabumi Regency.